(untitled) - Olds, C. D. (Washington, DC, 2000)
This is a self-contained introduction to the geometry of numbers. The authors gradually leads up to the theorems of Minkowski and others who succeeded him, and demonstrates how this powerful approach gives insight in a wide range of problems
Keywords: Geometry of numbers; Hình học đại số